Hydrothermal gasification of sewage sludge for hydrogen rich gas and solid fuel production - Wong, Wai Lun (2014)
Sewage sludge generation from wastewater treatment plants is soaring during rapid urbanization globally. Economical and environmentally friendly treatment and disposal of sewage sludge is becoming especially imperative. However, the high moisture content in the generated dewatered sewage sludge hinders the disposal and subsequent utilization as energy carrier. In the present project, hydrothermal processing technology has been employed to convert sewage sludge into various energy carriers (i.e. hydrogen rich fuel gas and solid fuel). Different hydrothermal conditions were applied to investigate the operating temperature and pressure on the evolution of different products. Results suggest that H2 and CH4 gas tended to become noticeable near-critical water while gasification was not favoured in subcritical water conditions. Meanwhile, the higher heating value of the hydrochars from the hydrothermal gasification of sewage sludge was much higher than that of dewatered sewage sludge. Due to dramatic reduction of nitrogen and sulphur in hydrochars, hydrochars can be a better candidate as solid fuels than dewatered sewage sludge.